2000
DOI: 10.1097/00001756-200006260-00006
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic 5′-nucleotidase hyperactivity in erythrocytes of Lesch–Nyhan syndrome patients

Abstract: Lesch-Nyhan syndrome is a metabolic-neurological syndrome caused by the X-linked deficiency of the purine salvage enzyme hypoxanthine-guanine phosphoribosyltransferase (HGPRT). Metabolic consequences of HGPRT deficiency have been clarified, but the connection with the neurological manifestations is still unknown. Much effort has been directed to finding other alterations in purine nucleotides in different cells of Lesch-Nyhan patients. A peculiar finding was the measure of appreciable amount of Z-nucleotides i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 7 publications
5
38
0
Order By: Relevance
“…These results were unexpected, because acadesine inhibits glucocorticoid-induced apoptosis in quiescent thymocytes, 16 apoptosis caused by serum deprivation in fibroblasts overproducing fructose 2,6-bisphosphate, 17 and ceramide-induced apoptosis in primary astrocytes. 18 In agreement with our results, recently it has been reported that acadesine causes apoptosis in 2 neuroblastoma cell lines 38 and a hepatoma cell line. 39 These results indicate that acadesine can either induce or inhibit apoptosis depending on the cell type.…”
Section: Discussionsupporting
confidence: 93%
“…These results were unexpected, because acadesine inhibits glucocorticoid-induced apoptosis in quiescent thymocytes, 16 apoptosis caused by serum deprivation in fibroblasts overproducing fructose 2,6-bisphosphate, 17 and ceramide-induced apoptosis in primary astrocytes. 18 In agreement with our results, recently it has been reported that acadesine causes apoptosis in 2 neuroblastoma cell lines 38 and a hepatoma cell line. 39 These results indicate that acadesine can either induce or inhibit apoptosis depending on the cell type.…”
Section: Discussionsupporting
confidence: 93%
“…Then the cycle is interrupted, causing IMP degradation by cN-II, and hypoxanthine accumulation. These results appear particularly relevant in light of our recent observations, showing that the Lesh Nyhan syndrome is metabolically related not only to a deficiency of HGPRT, but also to a three-to fivefold increase in cN-II [16]. At 2 mM initial PRPP concentration, the steady-state period lasted about 40 min, indicating that at both 1 and 2 mM PRPP initial concentrations, the velocity of the cycle remained unchanged ( fig.…”
Section: Resultssupporting
confidence: 63%
“…2017;39 (2) rs11191580 confers schizophrenia risk Low cN-II activity was also found to be present in the brain. 17 Pesi et al 18 reported that fluctuations in cN-II activity were involved with the pathological mechanism of Lesch-Nyhan syndrome, a metabolic-neurological syndrome related to hypoxanthine phosphoribosyl transferase deficiency. Moreover, a knockdown study in human astrocytoma cells revealed that cN-II activity was essential for their survival.…”
Section: Tablementioning
confidence: 99%